1989
DOI: 10.1111/j.1365-2842.1989.tb01367.x
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory and clinical evaluation of three dental luting cements

Abstract: The loss of material from specimens of three luting cements was measured after continuous erosion cycling in the laboratory. The glass ionomer luting cement showed significantly less material loss than the zinc polycarboxylate and zinc phosphate luting cements. Two hundred and fifty restorations cemented with one of the three materials were studied clinically for marginal integrity and retention over 3.5 years. The data were tested using survival analysis. Zinc phosphate cement gave the best clinical performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 13 publications
(9 reference statements)
2
7
0
1
Order By: Relevance
“…In this study, Meron (a glass polyalkenoate 63 (ionomer) cement) which included polyacrylic acid showed the significantly lowest solubility value than the other permanent cements. In other words, the solubility result of glass ionomer cement in this study corroborated those of previous studies 22,[36][37][38][39][40][41] . In an in vitro study, it was found that glass ionomer cement was more resistant to acidic erosion than polycarboxylate cement 42) .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In this study, Meron (a glass polyalkenoate 63 (ionomer) cement) which included polyacrylic acid showed the significantly lowest solubility value than the other permanent cements. In other words, the solubility result of glass ionomer cement in this study corroborated those of previous studies 22,[36][37][38][39][40][41] . In an in vitro study, it was found that glass ionomer cement was more resistant to acidic erosion than polycarboxylate cement 42) .…”
Section: Discussionsupporting
confidence: 82%
“…In an in vitro study, it was found that glass ionomer cement was more resistant to acidic erosion than polycarboxylate cement 42) . On the same issue about erosion, it was found in the present study that the percentage of solubility of polycarboxylate cement (3.989 ) was higher than that of glass ionomer cement (1.867 ) at pH 7 after 28 days, which corroborated reported findings that the solubility of polycarboxylate cement in water was relatively weaker 39,43) . With zinc phosphate cement, Mesu and Reedijk 36) stated that its biggest disadvantage was its greater solubility in the presence of organic acids of oral secretions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…7 However, clinical studies have failed to show any superiority of glass ionomer cements over zinc phosphate cements. 6,[8][9][10] Indeed, it was the development of dentin adhesives that revolutionized not only the world of direct restorations, but also that of indirect restorations. Adhesive bonding of restorations via a resin cement allowed new types of materials to be used for toothcolored and/or tooth-preserving restorations (eg, allceramic veneers and crowns, resin composite inlays/ onlays, resin-bonded bridges).…”
Section: Introductionmentioning
confidence: 99%
“…2,[5][6][7]11 Modifying powder/liquid ratio can have a dramatic effect on solubility. 25,35 This may explain reports of poor clinical performance of polycarboxylate cement, despite of relatively good performance in laboratory tests. Polycarboxylate cement material is thyrotrophic; i.e.…”
Section: Discussionmentioning
confidence: 90%